Innovating maharah kalam instruction through philosophical story-based role play: A quasi-experimental study - Faiqotul Millah; Lailatul Mathoriyah (Eduvista: Journal of Education and Innovation, 2026)
Maharah kalam remains a major challenge in Arabic language learning because instructional practices are still dominated by dialogue memorization, while the integration of philosophical stories as the contextual basis for role play has received limited scholarly attention. This study aims to examine the effectiveness of a role-play approach based on the philosophical story of Hayy bin Yaqdzon in improving students' maharah kalam. A quantitative approach employing a quasi-experimental pretest–posttest control group design was conducted with 65 students. Data were analyzed using descriptive statistics, normality and homogeneity tests, Normalized Gain (N-Gain), an independent-samples t-test, Cohen's d effect size, and a student response questionnaire. The findings revealed that the experimental group achieved a higher posttest mean (90.92) than the control group (84.55), a moderate N-Gain (0.5606), a significant difference (p < 0.001), a very large effect size (3.48), and positive student responses (77.35%). This study contributes by proposing a conceptual model explaining how philosophical storytelling strengthens the effectiveness of role play in improving maharah kalam. Abstrak Kemampuan maharah kalam masih menjadi tantangan dalam pembelajaran bahasa Arab karena pendekatan yang digunakan cenderung berorientasi pada hafalan dialog, sementara kajian mengenai integrasi cerita filosofis sebagai konteks role play masih sangat terbatas. Penelitian ini bertujuan menganalisis efektivitas pendekatan role play berbasis cerita filosofis Hayy bin Yaqdzon dalam meningkatkan maharah kalam siswa. Penelitian menggunakan pendekatan kuantitatif dengan desain quasi-experimental pretest–posttest control group design yang melibatkan 65 siswa, dengan analisis meliputi statistik deskriptif, uji normalitas, uji homogenitas, Normalized Gain (N-Gain), independent sample t-test, effect size (Cohen's d), dan angket respons siswa. Hasil penelitian menunjukkan bahwa kelas eksperimen memperoleh rata-rata posttest lebih tinggi (90,92) dibandingkan kelas kontrol (84,55), N-Gain kategori sedang (0,5606), perbedaan signifikan (p < 0,001), effect size sangat besar (3,48), serta respons siswa positif (77,35%). Penelitian ini berkontribusi dengan menawarkan model konseptual yang menjelaskan mekanisme integrasi cerita filosofis dalam memperkuat efektivitas role play untuk meningkatkan maharah kalam.